Determination of Lekethromycin, a Novel Macrolide Lactone, in Rat Plasma by UPLC-MS/MS and Its Application to a Pharmacokinetic Study - Hongzhi Xiao (Molecules, 2020)
Lekethromycin, a new macrolide lactone, exhibits significant antibacterial activity. In this study, a reliable analytical ultrahigh-performance liquid chromatography electrospray ionization quadrupole Orbitrap high-resolution mass spectrometry (UPLC-ESI-Orbitrap-MS) method was established and validated for the detection of lekethromycin in rat plasma. After a simple acetonitrile (ACN)-mediated plasma protein precipitation, chromatographic separation was performed on a Phenomenex Luna Omega PS C18 column (30 × 2.1 mm i.d. particle size = 3 μm) conducted in a gradient elution procedure using 0.5% formic acid (FA) in ACN and 0.5% FA in water as the mobile phase pumped at a flow rate of 0.3 mL/min. Detection was carried out under positive electrospray ionization (ESI+) conditions in parallel reaction monitoring (PRM) mode with observation of m/z 804.5580 > 577.4056 for lekethromycin and 777.5471 > 619.4522 for gamithromycin (internal standard, IS). The linear range was 5–1000 ng/mL (r2 > 0.99), and the lower limit of quantification (LLOQ) was 5 ng/mL. The intra- and inter-day precision (expressed as relative standard deviation, RSD) values were ≤ 7.3% and ≤ 6.3%, respectively, and the accuracy was ≥90% ± 5.3%. The mean extraction recovery RSD valWeue was < 5.1%. Matrix effects and dilution integrity RSD values were < 5.6% and < 3.2%, respectively. Lekethromycin was deemed stable under certain storage conditions. This fully validated method was effectively applied to study the pharmacokinetics of lekethromycin after a single intravenous administration of 5 mg/kg in rats. The main pharmacokinetic parameters were T1/2λz, CL_obs and VZ_obs were 32.33 ± 14.63 h, 0.58 ± 0.17 L/h/kg and 25.56 ± 7.93 L/kg, respectively.